SsRSS1 mediates salicylic acid tolerance and contributes to virulence in sugarcane smut fungus - Hao-yang ZHANG; Yan-fang YANG; Feng GUO; Xiao-rui SHEN; Shan LU; Bao-shan CHEN (Journal of Integrative Agriculture, 2023)
Sugarcane smut caused by Sporisorium scitamineum is a destructive disease responsible for significant losses in sugarcane production worldwide. However, the mechanisms underlying the pathogenicity of this fungus remain largely unknown. In this study, we found that the disruption of the SsRSS1 gene, which encodes a salicylic acid (SA) sensing regulator, does not affect phenotypic traits such as the morphology, growth rate, and sexual mating ability of haploid basidiospores, but rather reduces the tolerance of basidiospores to SA stress by blocking the induction of SsSRG1, a gene encoding a SA response protein in S. scitamineum. SsRSS1 deletion resulted in the attenuation of the virulence of the fungus. In addition to a significant reduction in whip formation, a portion of plantlets (18.3%) inoculated with the ΔSsRSS1 strains were found to be infected but failed to produce whips for up to 90 days post-inoculation. However, the development of hyphae and teliospore from the ΔSsRSS1-infected plants that formed whips seemed indistinguishable from that in the wild-type-infected plants. Combined, our findings suggested that SsRss1 is required for maintaining fungal fitness in planta by counteracting SA stress.